Ответы и объяснения

2012-11-14T06:31:08+00:00

Пусть,

f(x)=g(x)*h(x), где

 

g(x)=sgn(x);

h(x)=x^4-3x^2.

 

1.

Рассмотрим функцию g(x)=sgn(x)

sgn(x)=\begin{cases} -1; x \geq0 \\0; x=0\\ 1; x\leq0 \end{cases}

 

Отсюда: g(-x)

sgn(-x)=\begin{cases} -1; (-x) \geq0 \\0; (-x)=0\\ 1; (-x)\leq0 \end{cases }

Вследствие того, что

x<0  <=> (-x)>0 

x=0 <=> (-x)=0

x>0  <=> (-x)<0, имеем

sgn(-x)=\begin{cases} 1; x \geq0 \\0; x=0\\ -1; x\leq0 \end{cases}

sgn(-x)=-sgn(x)

 Функция g(x) - нечетная 2.

h(x)=x^4-3x^2

  h(-x)=(-x)^4-3(-x)^2=x^4-3x^2=h(x)   Функция h(x) - четная/ 3.

f(-x)=g(-x)*h(-x)=-g(x)*h(x)=-[g(x)*h(x)]=-f(x)

f(x)=-f(x) 

Ответ: функция f(x) - НЕЧЕТНАЯ